La Gestión de la Administración del talento humano y la evaluación del desempeño en la Coordinación Zonal del Ambiente, Agua y Transición Ecológica – NAPO. - Durán Gavilanes, Zuleyca Isabel (2022)
This present work was carried out with the objective of determining the incidence of the management of human talent administration and the evaluation of the work performance of the workers of the MAAE-Napo Zonal Coordination. The study population and sample consisted of 82 officials who work in the different work areas. The technique used for data collection was the survey, which is made up of a 14-item questionnaire of the two variables, designed with the use of nominal, ordinal and scale questions. The Human Talent Administration Management variable was made up of seven questions, as was the Performance Evaluation variable. In both cases with six categories and indicators for each of them. The study of this work is based on the quantitative approach of non-experimental design. The Chi square test originated that there is an association between the variables with a result of 0.015, it is concluded that the management of the administration of human talent and the evaluation of the work performance of the officials of the MAAE-Napo Zonal coordination does affect, since it is a process to stimulate and/or judge the value, excellence and qualities of a person emphasizing that it is an essential technique in the direction of each administrative activity.